2010
DOI: 10.4049/jimmunol.1002026
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Pcid2 in B Cell Survival through the Regulation of MAD2 Expression

Abstract: MaterialDNA damage occurring during proliferation is detected by a sensor mechanism, and the subsequent cell cycling is regulated by checkpoint proteins. Mitotic checkpoint proteins, such as MAD2, MAD1, and BUBR1, strictly regulate the cell-cycle progression of DNA-damaged cells by arresting kinetochore tension during mitosis (10). Thus, the expression of mitotic checkpoint proteins might be altered according to the various B cell differentiation stages.The GC-associated nuclear protein GANP is homologous to S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 35 publications
(26 reference statements)
0
16
0
Order By: Relevance
“…Knockdown of PolQ expression suppresses the DNA repair mechanism (46). Interestingly in our study, we witnessed a remarkable down-regulation of PolQ (47) which is involved in recruiting mitotic checkpoint proteins and regulating mitosis during DNA damage (48). In our study PCID2 was highly down-regulated which can be correlated to the inability of cells to overcome cell cycle arrest in the mitotic phase.…”
Section: Discussionmentioning
confidence: 47%
“…Knockdown of PolQ expression suppresses the DNA repair mechanism (46). Interestingly in our study, we witnessed a remarkable down-regulation of PolQ (47) which is involved in recruiting mitotic checkpoint proteins and regulating mitosis during DNA damage (48). In our study PCID2 was highly down-regulated which can be correlated to the inability of cells to overcome cell cycle arrest in the mitotic phase.…”
Section: Discussionmentioning
confidence: 47%
“…Pcid2 flox/flox mice were generated by homologous recombination as described . Pcid2 + /− mice were produced by crossing Pcid2 flox/flox mice with EIIa‐Cre transgenic mice.…”
Section: Methodsmentioning
confidence: 99%
“…Saccharomyces Thp1 is present in the ribonucleoprotein complex to participate in export of mRNAs from a nucleus to a cytoplasm . We recently reported that murine Pcid2 is selectively involved in the transport of MAD2 mRNA that regulates the mitotic checkpoint during B‐cell proliferation . A genome‐scale RNA interference (RNAi) screen identified Pcid2 as one of the genes that modulate self‐renewal of mouse ESCs (mESCs) .…”
Section: Introductionmentioning
confidence: 99%
“…Genes found to be required for spindle checkpoint control include the kinases BUB1 and BUBR1, the WD40 repeat containing protein BUB3, which directs the localization of the complex to kinetochores, and the APC inhibitors MAD2/CDC20. For example, loss-of-function of BUB1 , BUB3 and MAD2 results in increased polyploidy (32, 33). Moreover, although homozygous loss of Bubr1 leads to embryonic lethality, Bubr1 heterozygous mutant mice displayed splenomegaly and extramedullary megakaryopoiesis with a marked increase in polyploidization (34).…”
Section: Mks and The Endomitotic Processmentioning
confidence: 99%